Do community currencies enhance sustainable quality of life? - Mirijam Mock; Ines Omann; Felix Rauschmayer; Daniela Fuchs (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
Community currencies and their contribution to a sustainable development have been quite widely discussed. In contrast, their potential to raise the personal quality of life of their members and users has been less noted. Combining these two strands, we argue that community currencies enhance an individual sustainable quality of life. We underpin this by analysing data of an online survey of members and users of community currencies in Austria and Germany. The theoretical foundation of our analysis is the Capability Approach and its notion of quality of life, saying that a high quality of life is characterized by high freedom of choice of valuable doings and beings. A sustainable high quality of life would then be characterized by a high freedom of choice within the limits given by planetary boundaries and further sustainability criteria. This perspective allows inferringthat community currencies do not just contribute to sustainable development via their often emphasized effects in the field of regionalization and local value added, but in a much more encompassing way.
Keywords: 330